Modeling of Diesel Engine Fuel Systems Reliability When Operating on Biofuels - Zhuravel, Dmytro; Журавель, Дмитро Павлович; Samoichuk, Kyrylo; Самойчук, Кирило Олегович; Petrychenko, Serhii; Петриченко, Сергій Володимирович; Bondar, Andrii; Бондар, Андрій Миколайович; Hutsol, Taras; Kuboń, Maciej; Niemiec ,Marcin; Mykhailova, Lyudmyla; et al. (My University, 2025)
One of the maintrends in the developmentofmodernenginebuildingisthe useofbiodiesel fuel, which can lead to a decrease in the reliability of engines that are not adapted to it. However, at present there is no general method for determining the reliability of fuel systems of internal combustion engines. In this paper, a reliability model of engine fuel systems when operating on biofuel has been developed. Comprehensive indicators for assessing the reliability of diesel engine fuel systems are the coefficient of readiness and technical use. The availability factor of the fuel system when operating on biodiesel fuel without the replacement of structural materials was 0.66, while with the replacement it was 0.71, and the coefficient of technical utilization without replacement of materials was 0.36, and with the replacement of 0.4. Recommendations are given to improve the reliability of the engine fuel system components. The resulting model allows for complex comparisons of the effectiveness of various ways to improve the reliability of engines running on biodiesel fuel.
Keywords: biodiesel; reliability modeling; fuel system; state graph